Pengaruh Transfer Pricing dan Financial Distress Terhadap Tax Avoidance dengan Leverage Sebagai Variabel Moderasi : (Studi Empiris pada Perusahaan LQ 45 Yang Terdaftar di BEI Tahun 2017-2021) - Irawati Sianturi; Aris Sanulika (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
This study aims to examine the effect of Transfer Pricing and Financial Distress on Tax Avoidance with Leverage as a moderating variable in LQ 45 companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period. The independent variable in this study is Transfer Pricing (x1), Financial Distress (x2), the dependent variable is Tax Avoidance (Y) and the moderating variable is Leverage (Z). This study uses secondary data taken from annual reports of LQ 45 companies listed on the Indonesia Stock Exchange during the 2017-2021 period which can be seen on the website official, namely www.dx.co.id and journals or articles related to research objectives. The population in this study is LQ 45 companies listed on the IDX in 2017-2021 totaling 45 companies. The sample selection technique used a purposive sampling method, a sample of 20 companies was obtained with 100 observation data. Source of data is secondary data with quantitative methods. The analysis technique used is MRA with the help of the eviews version 12 application program. Based on the test results, this study states that (1) Transfer Pricing has an effect on Tax Avoidance (2) Financial Distress has no effect on Tax Avoidance (3) Leverage is unable moderate the effect of Transfer Pricing on Tax Avoidance (4) Leverage is unable to moderate the effect of Financial Distress on Tax Avoidance.